Targeted delivery of thermoresponsive polymeric nanoparticle-encapsulated lycopene: in vitro anticancer activity and chemopreventive effect on murine skin inflammation and tumorigenesis. Issue 28 (27th April 2020) - Bano, Sameena; Ahmed, Faheem; Khan, Farha; Chaudhary, Sandeep Chand; Samim, M.
Abstract : Nanolycopene demonstrated strong antioxidant activity and enhanced chemopreventive effect on skin tumorigenesis in mouse. Abstract : Naturally occurring lycopene has been reported for its chemopreventive and chemotherapeutic efficiency in various cancers, but its exceptional lipophilicity, poor aqueous solubility, instability, and consequently poor bioavailability limit its usage as a chemopreventive and chemotherapeutic agent. The present study aimed to synthesize co-polymeric nanoparticle-encapsulated formulations of commercial lycopene (NLY) and extracted lycopene (NLX) and evaluate their in vitro anticancer activity and inhibitory effect on 12- O -tetradecanoylphorbol-13-acetate (TPA)-promoted skin inflammation and tumorigenesis in Swiss albino mice. To prepare the nanoparticle-encapsulated formulations of lycopene, thermosensitive PNIPAAM–PEG-based co-polymeric nanoparticles were synthesized and characterized by FTIR spectroscopy, NMR spectroscopy, DLS, and TEM. Nanolycopene, unlike free lycopene, could be readily dispersed in aqueous media. Nanolycopene demonstrated stronger antioxidant activity and comparable in vitro anticancer efficacy to free lycopene against the melanoma cell line B16. Furthermore, nanolycopene showed comparable reduction of TPA-induced skin edema, expression of COX-2, and oxidative stress response. Additionally, it showed significant inhibition of tumor promotion. It also altered Bax and Bcl2 expressions, which led to the induction of apoptosis. The results also supported that the extracted lycopene-encapsulated nanoparticles may be a good alternative to the expensive commercial lycopene for cancer treatment.